Enhancing Photoluminescence of CsPb(ClxBr1−x)3 Perovskite Nanocrystals by Fe2+ Doping - Chang Wu; Yan Li; Zhengyao Xia; Cheng Ji; Yuqian Tang; Jinlei Zhang; Chunlan Ma; Ju Gao (Nanomaterials, 2023)
The doping of impurity ions into perovskite lattices has been scrupulously developed as a promising method to stabilize the crystallographic structure and modulate the optoelectronic properties. However, the photoluminescence (PL) of Fe2+-doped mixed halide perovskite NCs is still relatively unexplored. In this work, the Fe2+-doped CsPb(ClxBr1−x)3 nanocrystals (NCs) are prepared by a hot injection method. In addition, their optical absorption, photoluminescence (PL), PL lifetimes, and photostabilities are compared with those of undoped CsPb(Br1−xClx)3 NCs. We find the Fe2+ doping results in the redshift of the absorption edge and PL. Moreover, the full width at half maximums (FWHMs) are decreased, PL quantum yields (QYs) are improved, and PL lifetimes are extended, suggesting the defect density is reduced by the Fe2+ doping. Moreover, the photostability is significantly improved after the Fe2+ doping. Therefore, this work reveals that Fe2+ doping is a very promising approach to modulate the optical properties of mixed halide perovskite NCs.